PROSPECTS FOR THE DEVELOPMENT OF A MODERN PNEUMATIC DRYER OF SOLAR RADIATION TYPE AND THE PRINCIPLE OF ITS OPERATION - U. Qayumov (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article covers the experimental and theoretical studies, as well as the analysis of the use of pneumatic structures in rural areas and other sectors of the economy, and information on the principle of converting solar radiation into heat energy.